The handbook of intercultural discourse and communication - Paulston, Christina Bratt, 1932-; Kiesling, Scott F.; Rangel, Elizabeth S. (Malden, MA : John Wiley & Sons, 2012)
"The Handbook of Intercultural Discourse and Communication contains contributions from established scholars and up-and-coming researchers from a range of disciplines to survey the theoretical perspectives and applied work in this burgeoning area of linguistics. Features contributions from established researchers in sociolinguistics and intercultural discourse ; Explores the theoretical perspectives underlying work in the field ; Examines the history of the field, work in cross-cultural communication, and features of discourse ; Establishes the scope of this interdisciplinary field of study ; Includes coverage on individual linguistic features, such as indirectness and politeness, as well as sample analyses of IDC exchanges"--Provided by publisher.
Intercultural communication : an overview / Ingrid Piller -- Perspectives on intercultural discourse and communication / Leila Monaghan -- Cultures and languages in contact : towards a typology / John Edwards -- Interactional sociolinguistics : perspectives on intercultural communication / John J. Gumperz and Jenny Cook-Gumprez -- Ethnography of speaking / Scott F. Kiesling -- Critical approaches to intercultural discourse and communication / Ryuko Kubota -- Postmodernism and intercultural discourse : world Englishes / Suresh Canagarajah -- Turn-taking and intercultural discourse and communication / Deborah Tannen -- Silence / Ikuko Nakane -- Indirectness / Michael Lempert -- Politeness in intercultural discourse and communication / Janet Holmes -- Anglo-Arab intercultural communication / Eirlys E. Davies and Abdelali Bentahila -- Japan/Angle-American cross-cultural communication / Steven Brown, Brenda Hayashi, and Kikue Yamamoto -- "Those Venezuelans are so easy-going!" National stereotypes and self-representations in discourse about the other / Lars Fant -- "Face," stereotyping, and claims of power : the Greeks and Turks in interaction / Maria Sifianou and Arin Bayraktarglu -- Intercultural communication and vocational language learning in South Africa : law and healthcare / Russell H. Kaschula and Pamela Maseko -- Indigenous-Mestizo interaction in Mexico / Rocio Fuentes -- Translation and intercultural communication: bridges and barriers / Eiryls E. Davies -- Cultural differences in business communication / John Hooker -- Intercultural communication in the law / Diana Eades -- Medicine / Claudia V. Angelelli -- Intercultural discourse and communication in education / Amanda J. Godley -- Religion as a domain of intercultural discourse / Jonathan M. Watt.
Includes bibliographical references and index.
Print version record.
Keywords: Intercultural communication -- Handbooks, manuals, etc; Identity (Psychology); Social Science; Identity (Psychology); Intercultural communication; Discourse analysis; Interpersoonlijke communicatie; Interculturele communicatie; Electronic books; Handbooks and manuals